Water flow and water storage in Agave deserti: osmotic implications of crassulacean acid metabolism - Smith, J. A. C.; Schulte, P. J.; Nobel, P. S.
Water flow and water storage were investigated for Agave deserti, a desert succulent showing crassulacean acid metabolism (CAM). The anatomy and water relations of the peripheral chlorenchyma, where CAM occurs, and the central water-storage parenchyma were investigated for its massive leaves so that these tissues could be incorporated as discrete elements into an electrical-circuit analogue of the whole plant. The daily cycling of osmotic pressure was represented by voltage sources in series with the storage capacitors. With soil water potential and leaf transpiration rate as input variables, axial water flow through the vascular bundles and radial flows into and out of storage during the day/night cycle were determined.
Keywords: AGAVE DESERTI; CAPACITANCE; CRASSULACEAN ACID METABOLISM; ELECTRICAL-CIRCUIT ANALOGUE; LEAVES; OSMOTIC PRESSURE; RESISTANCE; TURGOR PRESSURE; WATER RELATIONS